Recombinant PAL/PilE/FlaA DNA vaccine provides protective immunity against Legionella pneumophila in BALB/c mice - Yingying Chen; Zehui Yang; Ying Dong; Yu Chen (BMC Biotechnology, 2020)
Abstract Background Legionella pneumophila (L.pneumophila), a Gram-negative small microorganism, causes hospital-acquired pneumonia especially in immunocompromised patients. Vaccination may be an effective method for preventing L.pneumophila infection. Therefore, it is necessary to develop a better vaccine against this disease. In this study, we developed a recombinant peptidoglycan-associated lipoprotein (PAL)/type IV pilin (PilE)/lagellin (FlaA) DNA vaccine and evaluated its immunogenicity and efficacy to protect against L.pneumophila infection. Results According to the results, the expression of PAL, PilE, FlaA proteins and PAL/PilE/FlaA fusion protein in 293 cells was confirmed. Immunization with PAL/PilE/FlaA DNA vaccine resulted in highest IgG titer and strongest cytotoxic T-lymphocyte (CTL) response. Furthermore, the histopathological changes in lung tissues of mice challenged with a lethal dose of L.pneumophila were alleviated by PAL/PilE/FlaA DNA vaccine immunization. The production of T-helper-1 (Th1) cytokines (IFNγ, TGF-α, and IL-12), and Th2 cytokines (IL-4 and IL-10) were promoted in PAL/PilE/FlaA DNA vaccine group. Finally, immunization with PAL/PilE/FlaA vaccine raised the survival rate of mice to 100% after challenging with a lethal dose of L.pneumophila for 10 consecutive days. Conclusions Our study suggests that the newly developed PAL/PilE/FlaA DNA vaccine stimulates strong humoral and cellular immune responses and may be a potential intervention on L.pneumophila infection.